Nitrous oxide fluxes from a commercial beef cattle feedlot in Kansas - Aguilar, Orlando A.; Maghirang, Ronaldo G.; Rice, Charles W.; Trabue, Steven L.; Erickson, Larry E. (My University, 2013)
Emission of greenhouse gases, including nitrous oxide (N₂O), from open beef cattle feedlots is becoming an environmental concern; however, research measuring emission rates of N₂O from open beef cattle feedlots has been limited. This study was conducted to quantify N₂O emission fluxes as affected by pen surface conditions, in a commercial beef cattle feedlot in the state of Kansas, USA, from July 2010 through September 2011. The measurement period represented typical feedlot conditions, with air temperatures ranging from −24 to 39°C. Static flux chambers were used to collect gas samples from pen surfaces at 0, 15, and 30 minutes. Gas samples were analyzed with a gas chromatograph and from the measured concentrations, N₂O fluxes were calculated. Median emission flux from the moist/muddy surface condition was 2.03 mg m⁻² hour⁻¹, which was about 20 times larger than the N₂O fluxes from the other pen surface conditions. In addition, N₂O peaks from the moist/muddy pen surface condition were six times larger than emission peaks previously reported for agricultural soils.
Keywords: Feedlot surface emissions; Greenhouse gases; Nitrous oxide flux; Static flux chambers